Slips, Trips and Falls among the workers in a garment industry in Dhaka, Bangladesh - Ali Kamal Mostofa Rubel; Sarmin Sultana; AKM Masum Ul Alam; Saika Nizam; Rabeya Yasmin; Sk Akhtar Ahmad; Mahmud Hossain Faruquee (Occupational Health and Safety Society of Nepal, 2021)
Introduction: Slips, trips and falls (STFs) lead to considerable accidents and injuries with a large financial consequence. In garment industries, occupational accidents and injuries are not uncommon and slips, trips and falls are the major contributory factors. It aimed to find out the contributing factors of slips, trips and falls among the garment workers in Bangladesh. Methods: This cross-sectional study was conducted in a garment industry to find out the factors responsible for slips, trips and falls among the workers. The study participants were garment workers with one year of experience, regardless of age and sex.  A total of 208 workers was selected by simple random sampling.  The study was conducted from July 2018 to June 2019. Results: Among the total 208 respondents, 130 (62.5%) were female and the mean age was 27.49±7.18 years. The majority of the respondents (57.2%) had a primary level of education and had work experience up to five years (71.6%). Of the total respondents, 62 (29.8%) had the experience of slips, trips and falls (STFs) in the last six months. Among them, slips were experienced by 34(16.3%), trips by 43(20.7%) and falls by 40(19.2%) respondents. Poor housekeeping 23(53.6%), mopped wet floor 18(52.9%), slopped and slippery floors 14(35.0%), improper storage 14(32.6%), uneven floor 12(30.0%) and spilling of drinks 9(26.5%) in a higher proportion were responsible for slips, trips and falls. The ergonomic factors which were reported to contribute to slips, trips and falls in a higher proportion were working posture 30(69.8%) and load-bearing 24 (60%). Workplace stress, on the other hand, was found to be the most common 37(92.5%) contributing factor to slips, trips and falls. Conclusion:   Almost two-thirds of garment workers experienced slips, trips and falls in their workplace. To prevent slips, trips and falls, steps should be taken to reduce the contributing factors, especially the workplace stress among the workers.